Perancangan Sistem Informasi Absensi Berbasis Website Dinas Komunikasi Informatika Statistik dan Persandian Menggunakan Metode Waterfall - Michael Oktavianus Hutabarat; M. Hadid Darmawan; Fadhil Hilmy Armanda; Nurtia Agustina (Universitas Ivet, 2024)
The Pekanbaru City Information, Statistics, and Coding Communication Service is increasingly aware of the importance of technology to increase efficiency and transparency in various aspects of their operations. One aspect that can be optimized is employee attendance. The presence of an attendance website in this agency functions to monitor employee attendance, permits and leave, holiday schedules and monitor attendance performance efficiently. Creating a successful attendance system can be accomplished in a variety of ways, one of which is through the use of computer technology and an information-based attendance application on a website. The waterfall method is used, and it includes investigation, plan, coding, testing, and upkeep. By fostering an electronic worker participation application, the Pekanbaru City Information, Communication, Statistics, and Coding Department can streamline the attendance process, reduce data loss, and eliminate errors in attendance data recording.